KEMAMPUAN GURU-GURU SEJARAH SMK DALAM MENYUSUN DAN MENGANALISIS SOAL - Fatmayanis Fatmayanis Fatmayanis (UNIVERSITAS BENGKULU, 2016)
This research aimed: (1) to know the teacher level ability in composing test items (2) to describe teachers’ ability in composing test items based on the taxonomy bloom level (3) to describe teachers’ ability in analyzing test items. This research was descriptive quantitative research. Collecting data for this research was using survey technique that used developed questionnaire instrument. The result of research shows: (1) the level of teacher ability in composing question in moderate category, (2) Teacher ability in composing low-level cognitive questions is good, (3) Teacher ability in analyzing test items is still low.Keywords: teacher ability, taxonomy bloom, test items analysis.